The significance and Risk Prediction of ABO Blood Group and Rh Factor in Differentiated Thyroid Carcinoma- Initial Experience at INMAS, Dhaka (Bangladesh Journal of Nuclear Medicine, 2025)
Objectives: Thyroid carcinoma occurs when abnormal cells in the thyroid gland start to divide and grow in an uncontrolled way. There are limited studies world-wide regarding the risk prediction of thyroid carcinoma with blood groups. In our study, we aimed to evaluate the significance and risk prediction of thyroid carcinoma with blood groups (ABO and Rh factor). Patients and Methods: The observational study included 100 thyroid carcinoma patients who came to INMAS, Dhaka for radioiodine ablation from January, 2022 to May, 2022. Results: Out of total 100 patients, 79 patients were females and 21 males. The age range of the patients was 17-65 years. 84 patients had classical variant papillary carcinoma (PCT), 5 had follicular variant papillary carcinoma (FV PCT), 4 had follicular carcinoma (FCT) and 7 had papillary microcarcinoma. Lymph node metastases (LNM) were found only among the classical variant PCT, 35 (41.66%) patients. Out of total 100 patients, blood group of 32 patients were B positive, 31 patients were O positive, 20 patients were A positive, 12 patients were AB positive, 3 patients were B negative, 1 patient was O negative and 1 patient was A negative. LNM were found in 13 (40.62%) patients of B positive, 7 (22.58%) patients of O positive, 7 (35%) patients of A positive, 5 (41.66%) patients of AB positive, 2 (66.66%) patients of B negative and 1 patient of A negative blood group. Conclusion: In our study, thyroid carcinoma is more common in B positive and O positive blood groups. In our country, B positive and O positive blood groups are common, so we could not conclude that these types of blood groups are more related with thyroid carcinoma than others.Bangladesh J. Nuclear Med. 27(2): 207-212, 2024